EFEKTIVITAS UPTD BALAI LATIHAN KERJA (BLK) DALAM MENINGKATKAN KUALITAS TENAGA KERJA DI UPTD BLK KABUPATEN PADANG PARIAMAN - Fahrani Yulzain; Jumiati Jumiati (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study aims to determine the effectiveness of UPTD Balai Latihan Kerja (BLK) in improving the quality of labor and the factors that influence the effectiveness of UPTD Balai Latihan Kerja (BLK) in improving the quality of the workforce at UPTD Balai Latihan Kerja (BLK) Kabupaten Padang Pariaman. Type of research is qualitative research with descriptive methods. The data source used in this study is primary data and secondary data. Techniques for collecting data on observation, interviews, and documentation. Test the validity of the data is using the source triangulation technique. The results of study showed that UPTD Balai Latihan Kerja (BLK) Kabupaten Padang Pariaman was quite effective in improving the quality of labor and the factors that influenced the effectiveness UPTD Balai Latihan Kerja (BLK) Kabupaten Padang Pariaman in improving the quality of labor were organizational characteristics, environmental characteristics, worker characteristics, and management policies and practices